2019
DOI: 10.1039/c8cc06967k
|View full text |Cite
|
Sign up to set email alerts
|

Stability of doubly and triply H-bonded complexes governed by acidity–basicity relationships

Abstract: The acidity–basicity interplay model allows explaining and tuning the relative stability of doubly and triply H-bonded complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In line with these results are the recent findings by Hernández‐Rodríguez, Rocha‐Rinza and co‐workers, who developed the acidity‐basicity interplay (ABI) model to explain the difference in association constants . In this model, the HB strength increases with the acidity of the proton donor and basicity of the proton acceptor groups.…”
Section: Energy Components In Hydrogen Bondssupporting
confidence: 75%
See 2 more Smart Citations
“…In line with these results are the recent findings by Hernández‐Rodríguez, Rocha‐Rinza and co‐workers, who developed the acidity‐basicity interplay (ABI) model to explain the difference in association constants . In this model, the HB strength increases with the acidity of the proton donor and basicity of the proton acceptor groups.…”
Section: Energy Components In Hydrogen Bondssupporting
confidence: 75%
“…They demonstrated that the SEI model ignores many significant (longrange) interactions, which led them to conclude that primary and secondary interactions constitute "a rather arbitrary subset".T he importance of considering additional atom-atom pairwise interactions has been confirmedb yo ther groups. [25,[81][82][83] Lukina nd Leszczynski [84] studied seventeen multiply H-bonded complexes to test the applicabilityo ft he SEI model,a nd concluded that "the stability information of a single complexc ould not be directly used to obtain stability data for H-bonded assemblies in general." Wu et al [84] showed with 26 triply and 20 quadruply H-bonded systemst hat the predictionsmade by the SEI model do not alwaysh old.…”
Section: Secondary Electrostatic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the SEI model is teaching material in organic chemistry textbooks , and is widely used in supramolecular chemistry to predict and explain the relative strengths of self-assembled systems. However, the validity of the model has been questioned, and the predicted trends in hydrogen bond stabilities are not always in line with experimental trends. Popelier and Joubert, Tiwari and Vanka, and most recently Hernández-Rodrı́guez, Rocha-Rinza, and co-workers , have demonstrated that all possible atom–atom interactions should be considered, not just the interactions between the frontier atoms as is done in the SEI model. Clark, Murray, and Politzer state that hydrogen bonds can be described in terms of Coulombic interactions, but only when the exact electronic density (or a reasonable approximation) is known and the polarization of each molecule is taken into account. , …”
Section: Introductionmentioning
confidence: 99%
“… 41 Rocha-Rinza and co-workers showed that the hydrogen bond strength is enhanced with increased acidity and basicity of the hydrogen bond donor and acceptor groups, respectively. 45 , 46 …”
Section: Introductionmentioning
confidence: 99%